2017
DOI: 10.1590/1983-21252017v30n429rc
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Phytoalexins in Beans, Soybeans and Sorghum by Fungal Filtrates

Abstract: The use of elicitors in plants for disease control is demonstrated by the accumulation of phytoalexins. Among these elicitors, metabolic products from fungi have been shown to be effective in the activation of mechanisms of induced resistance. Thus, this study aimed to evaluate the effects of filtrates from the saprobic fungi Curvularia inaequalis, Pseudobotrytis terrestris, Memnoniella echinata and Curvularia eragrostidis in inducing phaseolin, glyceolin and deoxyanthocyanidins. For this, fungal mycelial disk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…T. harzianum was applied on S. lycopersicum plants infected with A. cerealis . The filtrate sprayed after injecting tomato plants with A. cerealis conidial suspension (10 5 conidia/mL) [ 54 ]. Plant leaves were collected after 0, 2, 24, and 48 h for physiological assays and the plant were examined every 2 days until two weeks for any symptoms appearing.…”
Section: Methodsmentioning
confidence: 99%
“…T. harzianum was applied on S. lycopersicum plants infected with A. cerealis . The filtrate sprayed after injecting tomato plants with A. cerealis conidial suspension (10 5 conidia/mL) [ 54 ]. Plant leaves were collected after 0, 2, 24, and 48 h for physiological assays and the plant were examined every 2 days until two weeks for any symptoms appearing.…”
Section: Methodsmentioning
confidence: 99%
“…Isoflavonoids from the Leguminoseae family have been shown to have a defensive role as antibacterial phytoalexins against a wide range of pathogenic microorganisms [ 79 ]. Phaseolus vulgaris has been shown to produce phytoalexins such as phaseollin and kievitone in response to pathogen attack by the hemibiotrophic fungus Colletotrichum lindemuthianum , the causal of the bean anthracnose [ 80 ]. Additionally, the isoflavonoids medicarpin from Medicago sativa and pisatin from Pisum sativum represent similar examples from the Leguminoseae family.…”
Section: Plant Innate Immunity and Plant–pathogen Interactionmentioning
confidence: 99%
“…Solino and coauthors [22] evaluating the induction of phaseolin, gliceonin and deoxyanthocyanidins by filtrates of saprophytic fungi species Curvularia inaequalis, Pseudobitritis terrestris, Memnomiella echinata e Curvularia eragrostidis, obtained a phaseolin increment of 9, 8, 9 and 7% when compared to control.…”
Section: Effect Of Aes On Phaseolin Productionmentioning
confidence: 99%
“…Phytoalexins belong to different chemical classes that include flavonoids, polyacetylenes and isoprenes, including terpenoids and steroids [21]. In addition, studies with crude extract and essential oil of medicinal plants have indicated their potential in the induction of phytoalexins, besides showing fungitoxic action [22]. The effects of phytoalexins also are known in human health, where some chemical classes can promote GRAPHICAL ABSTRACT important effects in organism like antioxidant, antiaging, antitumor activities, or cardio and neuro protection [23].…”
Section: Introductionmentioning
confidence: 99%